Dignity, Social Reintegration of Prisoners, and the New Penal Power: European Human Rights, Experiences of Belgian Prisoners, and Professional Practices - Snacken, Sonja (International journal of offender therapy and comparative criminology, 2022)
Over the last 30 years, prisoners’ dignity and fundamental rights have increasingly been protected by European human rights bodies such as the European Court of Human Rights and the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment. This protection is aimed particularly at the traditional power relations between prisoners and uniformed staff. More recently, social reintegration of prisoners has also been recognized by these European human rights standards as a fundamental element of human dignity and an equally important aim of imprisonment as retribution and deterrence. However, it is also accepted that some offenders may be too dangerous to be returned back to society. Psychiatric/psychological assessments are a major element in this decision-making. This “new penal power” receives much less attention in human rights protection. This article compares three intertwining perspectives on this issue: the European human rights perspective on dignity and social reintegration; the experiences and mental suffering of Belgian prisoners who find themselves being stuck in prison as a result of structural problems in the risk assessment and risk management practices; and the professional perspective on how professional standards and good practices based on scientific insights might alleviate some of these threats to human dignity.